PENGARUH RELATIONAL BENEFITS TERHADAP SATISFACTION, TRUST, DAN ADVOCACY - Fatikhaturrohmah, Fatikhaturrohmah; Suharyono, Suharyono; Kusumawati, Andriani (PROFIT: JURNAL ADMINISTRASI BISNIS, 2020)
This article aims to review and explore information about research related to relational benefits, satisfaction, trust, and advocacy. Knowing about the effect of relational benefits on satisfaction, trust, and advocacy. Furthermore, knowing about the effect of satisfaction on trust and advocacy also the influence of trust on advocacy. Based on the results of several studies analyzed review, there are differences in influence between variables where it will have an impact not only on large-scale companies, but small-scale companies will also be affected. The factors that influence the relational benefits of satisfaction, trust, and advocacy are: confidence benefits, special treatment benefits, social benefits, convenience benefits, and safety benefits. These factors significantly influence satisfaction, trust, and advocacy. Furthermore satisfaction has a significant influence on trust and advocacy which is then followed by the results of a significant influence by trust on advocacy. But there is one researcher who gets the result that satisfaction does not have a significant effect on advocacy.